Pembinaan Atlet Muda Bulutangkis dengan Kejuaraan UNIBA CUP III Se-Karesidenan Besuki Tahun 2023 - Wawan Setiawan; Marki Sandi; Supono Supono; Yuni Fitriyah Ningsih (Universitas Negeri Surabaya, 2023)
Abstract: Badminton is a sport that is very popular with the community both as a daily sport and as a professional sport by many young Indonesians. This can be seen from the many young badminton athletes who have emerged and are also supported by Indonesia's badminton achievements on the world stage which are very proud of. With the achievements of these very good Indonesian athletes and to further maintain the competition for badminton achievements on the international stage, we PGRI Banyuwangi University intend to hold a SMA / SMK / MA Badminton Championships throughout Besuki Raya